2019
DOI: 10.1007/s13197-019-03637-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrolyzed water on enzyme activities of triticale malt during germination

Abstract: Triticale malt can be used as a source of enzymes or as a raw material for the production of functional foods. In this study, triticale malt was produced by soaking triticale seeds either in tap water (TW) or slightly acidic electrolyzed water (SAEW) and then rinsing with TW, SAEW, or alkaline electrolyzed water (AEW). We determined the length of the hypocotyl of triticale malt and the activities of a-amylase, phytase, proteases, and lipase during 4 days of germination. The electrolyzed water (EW) treatments p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…lycopersici) and also reduced the number of diseased fruits/plant, number of spots/fruit; and increased the number of healthy fruits/plant and total fruit yield/plant (Abbasi and Lazarovits, 2006) [63] . Yu and Liu, (2019) [64] found that electrolyzed water soaking improved the α-amylase activity, protease activity, phytase activity and lipase activity in triticale during seed germination.…”
Section: Effect Of Electrolyzed Water On Seed Decontamination and Seed Qualitymentioning
confidence: 99%
“…lycopersici) and also reduced the number of diseased fruits/plant, number of spots/fruit; and increased the number of healthy fruits/plant and total fruit yield/plant (Abbasi and Lazarovits, 2006) [63] . Yu and Liu, (2019) [64] found that electrolyzed water soaking improved the α-amylase activity, protease activity, phytase activity and lipase activity in triticale during seed germination.…”
Section: Effect Of Electrolyzed Water On Seed Decontamination and Seed Qualitymentioning
confidence: 99%
“…Previous studies have demonstrated the antibacterial potential of 1,8-cineole (SIMSEK & DUMAN, 2017). The germination of seeds is mainly related to amylase, lipase, and protease enzymes, which hydrolyze the starch, fat, and protein stored in the seeds to provide energy for germination (CENTENO et al, 2001;FASHUI et al, 2003;SIBIAN et al, 2017;yU & LIU, 2019). The starch content in the wheat seeds is high (KUMAR et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Diversos autores, al estudiar la capacidad del AEN para desinfectar las semillas de la alfalfa, el brócoli, el tomate, la lechuga y el arroz, encontraron que aumentaba el porcentaje de germinación y la calidad de las plantas en desarrollo(Abbasi & Lazarovitz, 2006;Kim, Feng, Kushad & Fan, 2006;Liu et al, 2013;Zhang et al, 2019;Guerra, Villalba, Contreras, Debasis & Sandoval, 2022). Los autoresYu & Liu (2019), concluyeron que al emplear el AEN en los pretratamientos, se incrementaba la actividad de la α-amilasa, de las proteasas, de las fitasas y las lipasas en el cereal triticale. Asimismo,Li et al (2018), indicaron que al aplicar el AEN a 40 mg/L durante rutina, que son los metabolitos secundarios generados durante el proceso germinativo y desarrollo de las plántulas.…”
unclassified